DASH Diet Education for Improvement in Hypertensive Outcomes - Smith, S.J. (My University, 2020)
Hypertension is a leading risk factor for cardiovascular disease (AHA, 2015). Although hypertension is a modifiable risk factor, 54% of an estimated one million adults with hypertension have poorly controlled hypertension (CDC, 2017). Lifestyle modification, such as the Dietary Approach to Stop Hypertension (DASH) diet, have demonstrated reduced blood pressure (National Heart Lung Blood Institute, 2015). This project introduced the DASH diet plan to pre-hypertensive and hypertensive employees of a corporation that utilizes an onsite workplace clinic. The structured education was scheduled for 8-weeks of bi-weekly sessions. This project aimed to determine if a structured DASH education program along with DASH reference pamphlets would improve knowledge and awareness, change eating habits, and subsequentially show a reduction in diastolic and systolic blood pressure. The results indicated that nine of the 27 participants had a reduction in diastolic and systolic blood pressure. Ninety-six percent responded that they understood the relationship between DASH nutrition and blood pressure. The post-education food frequency questionnaire showed 33% (11) responded had increased consumption of fruits, vegetables, and grains by two or more servings. The findings indicated that a structured DASH intervention could be successful in changing attitudes and knowledge about nutrition, and showed a positive impact on the reduction of blood pressure.
Keywords: DASH; Diet; Hypertension; Education; Blood pressure; Nutrition; Lifestyle modification; Patient education; Adherence; Risk factors; Prevention; Heart disease; Stroke; Cardiovascular disease